PENGARUH JUMLAH WAJIB PAJAK TERDAFTAR DAN JUMLAH SPT TERLAPOR TERHADAP PENERIMAAN PAJAK PENGHASILAN PASAL 21 PADA KPP PRATAMA PALEMBANG ILIR BARAT - Rosalina Pebrica Mayasari (Universitas Indo Global Mandiri)
The research objective is to understand the influence of the Number of Taxpayer and the Number of Annual Tax Return on the Quantity of Personal Income Tax. Research type is explanatory research with quantitative approach. Secondary data are used, the data collection technique is documentation, analysis method by using multiple linear regression. The population in this research is Quantity of Personal Income Tax period 2005-2014. The Result of research indicated that the Number of Taxpayer, and the Number of Annual Tax Return have significant effect simultaneously on the Quantity of Personal Income Tax. Partially, the number of taxpayer and the Number of Annual Tax Return has no significant influence on the Quantity of Personal Income Tax.